Pendidikan Inklusif dalam Al-Qur’an: Membangun Kecerdasan Interpersonal Penyandang Disabilitas: Inclusive Education in the Qur'an: Building Interpersonal Intelligence in People with Disabilities - Maki, Zaini (Epistemic: Jurnal Ilmiah Pendidikan, 2024)
Inclusive education aims to ensure that all children, including people with disabilities, receive a proper education in formal schools. However, challenges often arise if parents and teachers do not understand the needs of children with disabilities. This article examines the Qur'an's view of inclusive education and how its principles can help build the interpersonal intelligence of people with disabilities. With the tafsîr maudu'î ala al-Farmawi method, this study found that the Qur'an emphasizes the importance of diversity and mutual respect. The concepts of spiritual, emotional, and social intelligence in the Qur'an support the development of positive and inclusive interactions. The Qur'an teaches that glory in the sight of Allah is determined by obedience and attitude, not physical aspects. Principles such as brotherhood (ukhuwwah), compassion (shilah al-rahim), good communication (qaulan sadîd?), and forgiveness (al-'afw) play a role in creating an inclusive educational environment. This research shows how the application of these principles can improve the understanding and integration of people with disabilities in education, as well as promote a more empathetic and supportive environment.